2000
DOI: 10.1161/01.atv.20.8.1932
|View full text |Cite
|
Sign up to set email alerts
|

Race, Visceral Adipose Tissue, Plasma Lipids, and Lipoprotein Lipase Activity in Men and Women

Abstract: Abstract-Abdominal obesity is associated with numerous metabolic alterations, such as hypertriglyceridemia and low levels of high density lipoprotein (HDL) cholesterol. However, compared with abdominally obese white individuals, abdominally obese black individuals have been characterized by higher plasma HDL cholesterol levels, suggesting that the impact of abdominal fat accumulation on the lipoprotein-lipid profile may differ among ethnic groups. Therefore, we have compared the associations between body fatne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
122
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(147 citation statements)
references
References 38 publications
(34 reference statements)
15
122
1
9
Order By: Relevance
“…The ethnic differences found in both TC and TG levels confirm results from previous studies in both non-pregnant (Zoratti, 1998;Despres et al, 2000;Lamon-Fava et al, 2005) and pregnant women (Koukkou et al, 1994), reporting more favourable TC and TG levels in African/Afro-Caribbean women as compared with Caucasian women. Taylor et al (1987) found a significant difference in TG levels between postpartum African-Caribbean and Indian-Caribbean women, which is similar to our observations for African-Caribbean and Surinam-Hindustani women.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The ethnic differences found in both TC and TG levels confirm results from previous studies in both non-pregnant (Zoratti, 1998;Despres et al, 2000;Lamon-Fava et al, 2005) and pregnant women (Koukkou et al, 1994), reporting more favourable TC and TG levels in African/Afro-Caribbean women as compared with Caucasian women. Taylor et al (1987) found a significant difference in TG levels between postpartum African-Caribbean and Indian-Caribbean women, which is similar to our observations for African-Caribbean and Surinam-Hindustani women.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies have shown that the accumulation of central fat is more associated with abnormal lipid/lipoprotein profile compared with a general fat distribution (Seidell et al, 2001;Snijder et al, 2004b;Canoy et al, 2006). The ethnic differences might be explained by the variability in fat deposition, that is visceral vs subcutaneous accumulation (Despres et al, 2000;Snijder et al, 2004a, b). For instance, Ghanaian women have more subcutaneous fat deposits compared with Caucasian women and also the lowest TC and TG levels (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52] Despite higher HDL-C levels, white women in this study had a more atherogenic lipid profile than black women. 50,53 We reported that the relationship between the TNFA -238 G4A polymorphism and serum LDL-C and T-C concentrations differed, depending on the intake of the n-3 PUFA's EPA and DHA, in white but not in black women.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, women store more subcutaneous fat in the gluteal-femoral region, whereas men store more fat in the abdominal-visceral depot. 36 CRP levels are more closely correlated with visceral fat than with subcutaneous fat. 34 When men and women lose BW after exercise training, men reduce more from the abdominal-visceral fat depot, whereas women reduce more subcutaneous fat; 37 hence, our result showing no gender difference in hsCRP reduction may be attributed to greater reduction in abdominal fat in men than in women.…”
Section: Mechanisms Of Lack Of Gender Difference In Hscrp Reductionmentioning
confidence: 91%